Product Innovation and Halal Lifestyle Identity: An Ethnographic Study of the Sharia Marketing Strategy of Swarnabhumi Batik Ecoprint MSMEs in the ISEF Event - Nola Rahma Alhamda; Anita Sumelvia Dewi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study analyzes the sharia marketing strategy of Swarnabhumi MSMEs through the integration of environmentally friendly ecoprint innovations with a halal lifestyle concept at the 2025 Indonesia Sharia Economic Festival (ISEF) event. Using a qualitative ethnographic approach with interviews, observations, and data triangulation. The findings of this study indicate that there was an increase in turnover from 15 million to 20 million thanks to halal certification and business matching at the event. The results of this study provide practical guidance for sharia economic MSMEs to implement halal-certified marketing strategies to be more competitive in the domestic market and exports through events such as the Indonesia Sharia Economic Festival.